Physical properties and cellular responses of gelatin methacryloyl bulk hydrogels and highly ordered porous hydrogels - Yin, Haiyan; Zhu, Mengxiang; Wang, Yingying; Luo, Lihua; Ye, Qingsong; Lee, Bae Hoon (Frontiers in Soft Matter, 2023)
Protein-based hydrogels hold a high content of water in their three-dimensional (3D) network structure and exhibit innate biological activities as well as soft tissue-like mechanical properties, resulting in being highly applicable to various tissue engineering fields. However, precisely controlling the 3D porous structure of protein-based hydrogels remains a challenging task, and understanding the influence of their porous structure on physical properties and cellular responses is crucial for tissue engineering applications. In this study, we prepared highly ordered gelatin methacryloyl hydrogels with regular interconnected pores and traditional bulk hydrogels with irregular pores to evaluate their differences in physiochemical properties and cellular behaviors. Highly ordered gelatin methacryloyl hydrogels exhibited a high degree of compliance owing to their sponge-like structure whereas gelatin methacryloyl bulk hydrogels exhibited relatively higher moduli but were brittle due to a densely packed structure. The highly ordered gelatin methacryloyl hydrogels with interconnected pores supported higher cell viability (about 100%) due to an efficient flux of oxygen and nutrients compared to the dense bulk hydrogels showing cell viability (around 80%). Also, cells in the highly ordered gelatin methacryloyl hydrogels displayed a more stretched morphology compared to those in the gelatin methacryloyl bulk hydrogels that exhibited a more round morphology during the cell culture period.